Analisis Pengaruh Faktor-Faktor Fundamental dan Resiko Sistematis terhadap Stock Return PT. Astra Agro Lestari Tbk. (Period 2000 – 2009) - Erna B. Sitanggang dan Elsya Meida Arif (Jurnal Manajemen FE-UB, 2017)
The purpose of this study is to examine the effect of financial fundamental factors and systematic risk to stock return of PT. Astra Agro Lestari Tbk. using time series data period 2000 – 2009.  Financial fundamental factors used in this study are return on equity (ROE), earning per share (EPS), price earning ratio (PER), price book value (PBV), debt equity ratio (DER) and beta, and stock return as dependen variable. This research uses multiple regression model to test the hypotheses.            This study provides evidence that financial fundamental factor ROE has positif and significant effect on stock return. This result indicates that increasing a equity value will increase stock return. And the study the effect of systematic risk on the stock return provide evidence of a positif effect but not significant to PT. Astra Agro Lestari Tbk stock return. Keywords: Financial fundamental factors, Price earning ratio (PER), Book Value (BV), Return on Equity (ROE), Systematic risk (beta), and stock return.